2019
DOI: 10.1080/09593985.2019.1685035
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent impact of bilateral multiple joint functional electrical stimulation and treadmill walking on gait and spasticity in post-stroke survivors: a pilot study

Abstract: Background: Stroke causes multi-joint gait deficits, so a major objective of post-stroke rehabilitation is to regain normal gait function. Design and Setting: A case series completed at a neuroscience institute. Aim: The aim of the study was to determine the concurrent impact of functional electrical stimulation (FES) during treadmill walking on gait speed, knee extensors spasticity and ankle plantar flexors spasticity in post-stroke survivors. Participants: Six post-stroke survivors with altered gait patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…In a recent study, relief of spasticity in patients with spinal cord injury was observed for 4 h following 30 min of FES and TENS application, and it was reported that there was no significant difference between the two methods [ 11 ]. However, in the case of FES, there is insufficient evidence regarding its ability to reduce spasticity, especially in patients with stroke [ 9 , 12 , 13 ]. Recently, many studies have reported that TENS [ 14 , 15 ] and taping [ 16 18 ] are effective interventions for the management of spasticity associated with neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, relief of spasticity in patients with spinal cord injury was observed for 4 h following 30 min of FES and TENS application, and it was reported that there was no significant difference between the two methods [ 11 ]. However, in the case of FES, there is insufficient evidence regarding its ability to reduce spasticity, especially in patients with stroke [ 9 , 12 , 13 ]. Recently, many studies have reported that TENS [ 14 , 15 ] and taping [ 16 18 ] are effective interventions for the management of spasticity associated with neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Static balance was evaluated by the adjusted Romberg test (McIlroy and Maki, 1997). Dynamic balance was measured using the Timed Up & Go test in which the participants were required to rise from the chair, walk three meters, turn around, walk back to the chair and sit down (Hakakzadeh et al, 2019).…”
Section: Measurements (Primary Outcomes)mentioning
confidence: 99%
“…There are many available modality and movement therapies of post-stroke rehabilitation that have positive effects on motor and gait functions in patients after stroke, e.g., cycling, treadmill walking and functional electrical stimulation [ 8 , 9 ]. However, they may be expensive and provide a limited kind of movement.…”
Section: Introductionmentioning
confidence: 99%